300 GHz optical waveform measurement by novel THz‐wave autocorrelator. Issue 11 (1st May 2020) - Yamamoto, R.; Ichiyama, K.; Che, M.; Kuboki, T.; Ito, H.; Ishibashi, T.; Kato, K.
Abstract : A novel THz‐wave autocorrelator consisting of an optical delay line and high‐speed photodiodes was proposed for the measurement of optical waveforms with a high rate of repetition. In this system, the waveform is delayed at the optical domain and correlated at the THz domain. Experimental results show clear autocorrelations of 100, 200 and 300 GHz sinusoidal waveforms which indicate the feasibility of the proposed method.